Effect of simultaneous intravitreal ranibizumab and extended-release dexamethasone injection on patients with naïve versus refractory retinal vein occlusion macular edema: a prospective, multicenter, and interventional open-label study - Yao-Yao Sun; Jie Meng; Shan-Shan Li; Qin Xiao; Tian-Zi Zhang; Heng Miao; Ming-Wei Zhao; Hui-Jun Qi (International Journal of Ophthalmology)
AIM: To evaluate the efficacy and safety of concurrent intravitreal ranibizumab (IVR) and extended-release dexamethasone injections (Dex-I) in naïve and refractory patients with retinal vein occlusion macular edema (RVO-ME). METHODS: This was a prospective, interventional, and open-label clinical trial. There were two groups: naïve and refractory patients (received ≥5 times of previous IVR within one year prior to enrollment) enrolled. Patients received IVR and Dex-I concurrently and re-combination therapy was required if one or more retreatment criteria were met. IVR and Dex-I were given pro re nata (PRN). The mean changes in best-corrected visual acuity (BCVA) and central macular thickness (CMT) were measured as main outcomes. RESULTS: Totally 63 patients (63 eyes) completed the entire follow-up (31 naïve and 32 refractory patients). At month 12, the change in BCVA was greater in the naïve group than in the refractory group [19.67±11.7 (95%CI: 15.03, 24.31) letters vs 11.74±11.18 (95%CI: 7.32, 16.16) letters, P=0.014). There was no difference between the two groups of mean macular thickness reduction [364.26±215.29 (95%CI: 279.09, 449.43) μm vs 410.19±204.34 (95%CI: 329.35, 491.02) μm, P=0.43). The mean co-injection numbers were 2.52±0.58 (95%CI: 2.29, 2.75) and 2.33±0.55 (95%CI: 2.11, 2.55) in both groups (P=0.24), respectively. The retreatment interval was 115.81±13.79 d (95%CI: 110.36, 121.27) and 122.74±14.06 d (95%CI: 119.93, 133.56) in both groups (P=0.073). There was no significant difference in the incidence of glaucoma or the progression of cataracts between the two groups. CONCLUSION: In both naïve and refractory RVO-ME patients, IVR combined with Dex-I is effective. The initial combination therapy for naïve patients demonstrates more efficient improvement in BCVA and may reduce total injection numbers compared to refractory patients.